Metal-free synthesis of 1, N6-ethenoadenines from N6-propargyl-adenines via NIS mediated radical cascade reaction. Issue 66 (26th November 2019) - Yang, Ruchun; Deng, Si; Dong, Xiang-you; Song, Xianrong; Cai, Hu; Bai, Jiang; Xiao, Qiang
Abstract : An efficient approach for the construction of 1, N 6 -ethenoadenines is developed through the metal-free mediated radical cascade cyclization of conveniently prepared N 6 -propargyl-adenines. Abstract : In the present paper, an efficient approach for the construction of 1, N 6 -ethenoadenines from conveniently prepared N 6 -propargyl-adenines is developed. This reaction merges N -iodosuccinimide radical initiation and aerobic aminooxygenation in dioxane. This mild, 5-exo-dig, and metal-free cascade reaction could be applied to a wide substrate scope to provide 1, N 6 -ethenoadenines in moderate to good yields. The reaction mechanism was proposed and tested using radical inhibitor (butylated hydroxytoluene) and isotopic labelling ( 18 O2 ) experiments.